Formation of an SEI on a LiMn2O4 cathode during room temperature charge-discharge cycling studied by soft X-ray absorption spectroscopy at the Fluorine K-edge - Chung, Kyung Yoon; Yoon, Won-Sub; Kim, Kwang-Bum; Cho, Byung-Won; Yang, Xiao-Qing (SPRINGER, 2011)
The solid electrolyte interface (SEI) formation on the surface of LiMn2O4 electrodes during room temperature charge-discharge cycling was studied using soft X-ray absorption spectroscopy at the Fluorine (F) K-edge. LiMn2O4 electrodes without any binder were prepared by electrostatic spray deposition to eliminate the signal originating from the PVDF binder in the F K-edge X-ray absorption spectra. The F K-edge absorption spectra show that the SEI layer forms at a very early stage of cycling. SEI growth takes place during discharge. In addition, LiF formation is accelerated if the discharge step follows a charge step. The F K-edge absorption spectra suggest that the major component of the SEI is LiF.
Keywords: THIN-FILM ELECTRODES; STRUCTURAL FATIGUE; SPINEL ELECTRODES; CAPACITY LOSSES; BATTERIES; PERFORMANCE; OXIDES